Economic, social and environmental consequences of the use of genetically modified organisms - Kenzhin, Zh. B.; Tsaurkubule, Zh.; Tuleugaliyeva, N. I.; Domalatov, Ye. B. (Bulletin of the Karaganda university /сер. экон./. - 2021, 2021)
Object: to analyze the effectiveness of the use of genetically modified organisms in terms of economic efficiency, as well as environmental and social consequences. Methods: a theoretical review of the scientific literature on the research topic. Results: on the basis of literature data arguments are presented in favor and against the introduction of genetic modification technology in agriculture. Potential benefits and risks this technology may entail are considered. Conclusions: it has been established that genetic modification of crops provides multiple benefits, contributing to the simplification of production processes, an increase in profit margins, and a reduction in losses caused by diseases and pests. Lower cultivation costs, in turn, lead to lower food prices, which may be the key to solving the issue of hunger in developing countries. It was revealed, among other things, that the use of genetically modified crops not only does not harm biological diversity, but, on the contrary, contributes to its expansion. The findings could be utilized when justifying a regional agricultural development program.
Keywords: рк; agriculture; agro-industrial complex economics; genetic engineering; gmo; biotechnology; economic efficiency; crops; отечественное издание; научный журнал; периодическое издание; журнал коксон